Investigating the Role of Translationally Control Tumor Protein in Growth, Development and Differentiation of Dictyostelium discoideum - Kumar, Rakesh; Maurya, Ranjana; Saran, Shweta (Frontiers in Cell and Developmental Biology, 2020)
Translationally controlled tumour protein (TCTP) is a multifunctional protein implicated in various types of cellular processes involving growth and development of an organism. Here, we identified tctp gene in Dictyostelium discoideum and unravelled its function. The sequence analysis of D. discoideum TCTP (DdTCTP) showed its conservation among eukaryotes. Transcript of DdTCTP were highly expressed at the initial time points of development and protein was localized both in the cytoplasm and nucleus. Disruption of tctp was achieved by BSR cassette using double homologous recombination method. Abrogation of tctp resulted in reduced cell proliferation but increased cell size. Additionally, development was delayed by 4 hours wherein small-sized aggregates and fruiting bodies were produced by tctp־ cells while larger aggregates and fruiting bodies were produced by tctpOE cells concordant with the fact that TCTP regulates prestalk/prespore ratio and cell-type differentiation. tctp־ cells produced round spores with reduced viability and stalk cells are arranged in septate pattern as compared to polyhedral manner of wild type. Abrogation of tctp resulted in aberrant localisation of cell type specific markers and show less proclivity towards prespore/spore region, in presence of wild type cells.